2023
DOI: 10.3390/cells12141862
|View full text |Cite
|
Sign up to set email alerts
|

ROP16 of Toxoplasma gondii Inhibits Innate Immunity by Triggering cGAS-STING Pathway Inactivity through the Polyubiquitination of STING

Abstract: cGAS-STING signaling is a major pathway in inducing type Ⅰ IFN, which plays a crucial role in the defense against T. gondii infection. In contrast, T. gondii develops multiple strategies to counteract the host defense, causing serious diseases in a wide range of hosts. Here, we demonstrate that T. gondii rhoptry protein 16 (ROP16) dampens type I interferon signaling via the inhibition of the cGAS (cyclic GMP-AMP synthase) pathway through the polyubiquitination of STING. Mechanistically, ROP16 interacts with ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…ROP16 can polyubiquitinate STING, resulting in inactivate cGAS-STING signaling pathway [ 54 ]. In this way, STING was inactivated and subsequently decreased the secretion of inflammatory cytokines, downregulating the STAT1 and NF-κB pathways in brain metastatic cells, thereby suppressing the brain metastasis of breast cancer and lung cancer [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROP16 can polyubiquitinate STING, resulting in inactivate cGAS-STING signaling pathway [ 54 ]. In this way, STING was inactivated and subsequently decreased the secretion of inflammatory cytokines, downregulating the STAT1 and NF-κB pathways in brain metastatic cells, thereby suppressing the brain metastasis of breast cancer and lung cancer [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether other effector molecules of T. gondii also play a negative regulatory role in the stage of co-infection needs to be considered and further studied. Recently, research reported that ROP16 II diminished IFN-I signaling, which independent on its kinase activity, via the inhibition of the cGAS pathway by suppressing K63-linked ubiquitination of STING ( Figure 2 ) ( 70 ). However, the dense granule protein 15 (GRA15 II ), another protein from T. gondii , promotes STING polyubiquitination at Lys-337 and STING oligomerization through a TRAF protein–dependent process, and subsequently enhances the host DNA/cGAS/STING pathway against T. gondii infection ( Figure 2 ) ( 71 ).…”
Section: Regulations Between Ifn-i and T Gondiimentioning
confidence: 99%